Analyzing Determinants of Construction Project Resilience and Success in Ethiopia: a Structural Equation Modelling Approach (PLS-SEM) - Bekele Desta, Kebede; Lunga, Msengana (International Journal of Engineering and Management Sciences, 2026)
The purpose of this study is to investigate the factors that contribute to the success and resilience of construction projects in Ethiopia’s construction industry. A major gap exists in the current literature regarding the empirical validation of the relationships between resilience and success in the Ethiopian construction industry. Data collection was conducted via an online survey between March 8th and May 13th, 2024. PLS-SEM analysis was performed on the survey responses. Results indicate that resilience significantly impacts a project’s success. The following are resilience-enabling factors that increase a project’s resilience and enhance overall project performance. These are: resilient leadership (taking risks; learning from subordinates; being flexible during decision making); organisational structures (having few direct reports; narrow span of control; job rotation); and project team culture (assign right people for right jobs; recognition or rewarding the team members; team passions for contribution for project success; team trusts); external environment factors (mitigating high inflation effect; managing unstable economy; using appropriate legal enforcement); and risk management practices (communicating frequently; understanding/knowing how to implement risk management practices; integrating risk management practices into routine activities; having enough budget/finance). Success indicators for construction projects include quality, cost, time, safety and customer satisfaction. Therefore, developing resilience-enhancing strategies could greatly increase the effectiveness of construction project performance. The contribution of this study includes empirical evidence from the Ethiopian context, as well as practical recommendations for policymakers and project managers to create customised resilience strategies. The limitations of this study include reliance on self-reported data and convenience sampling in collecting survey responses. Overall, the study emphasizes the importance of resilience in overcoming the challenges of the construction industry in Ethiopia.